BMT Maslahah's Contribution to the Economic Development of the Community in the Surrounding Area - Sholihatul Umaroh; Roghiba Fillah; M. Dayat (Journal of Economic, Management and Entrepreneurship, 2025)
Sharia cooperatives are cooperative institutions that carry out all business activities, financial management and member services based on Islamic sharia principles.The purpose of this study is to explore and explain how to apply SWOT analysis to the Wonorejo branch of the BMT Maslahah Cooperative in order to support the development of the people's economy in the Wonorejo District area. The results of these activities demonstrate that BMT Maslahah plays a crucial role in strengthening the community's economy through the provision of microfinance, business mentoring, and increasing Sharia financial literacy. This research uses qualitative research. The tangible impact is evident in the increased business capacity of members, the creation of new economic opportunities, and growing public awareness of Sharia-compliant financial practices. Thus, the presence of BMT Maslahah has been proven to provide a positive and sustainable contribution to the economic development of the community in its environment